Takotsubo syndrome and cardiac implantable electronic device therapy - El-Battrawy, Ibrahim; Erath-Honold, Julia; Lang, Siegfried; Ansari, Uzair; Behnes, Michael; Gietzen, Thorsten; Zhou, Xiao-Bo; Borggrefe, Martin; Akın, Ibrahim (Scientific reports, 2019)
Recent studies have reported that takotsubo syndrome (TTS) patients are suffering from life-threatening arrhythmias. The aim of our study was to understand the short and long-term usefulness of cardiac implantable electronic devices in TTS patients.We constituted a collective of 142 patients in a bi-centric study diagnosed with TTS between 2003 and 2017. The patient groups, divided according to the treatment with (n = 9, 6.3%) or without cardiac devices (n = 133, 93.7%), were followed-up to determine the importance of devices and its complications. One patient was treated with a permanent pacemaker, five patients with a wearable cardioverter defibrillator, two patients with a subcutaneous defibrillator and one patient with a transvenous defibrillator. Regular device check-up was documented in all patients, presenting an ongoing high-degree AV-block. Neither device complications nor life-threatening tachyarrhythmias were documented after acute TTS event. However, patients comprising the device group suffered significantly more often from a highly reduced EF (30 ± 7.7% versus 39.1 ± 9.7%; p < 0.05), cardiogenic shock with use of inotropic agents (66.6% versus 16.6%; p < 0.05) and cardiopulmonary resuscitation (44.4% versus 5.3%; p < 0.05). Our data confirm the usefulness of pacemaker in TTS patients. However, the cardioverter defibrillator including wearable cardioverter defibrillator may not be recommended.
Gesehen am 02.03.2020